MELIOIDOSIS AND DIABETES MELLITUS IN HOSPITAL TELUK INTAN: AN AUDIT OF OUTCOMES AND THEIR ASSOCIATION WITH GLYCEMIC CONTROL - Sun, Choon Peng; Mokhtar, Nor Akmal; Kamarudin, Aida Syahirah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Melioidosis, caused by Burkholderia pseudomallei, is endemic in tropical climates and poses a heightened risk to individuals with diabetes mellitus, particularly those with poor glycemic control. Diabetes is a well-established risk factor for severe melioidosis, often resulting in worse clinical outcomes. This audit aims to assess the prevalence, clinical outcomes, and the relationship between glycemic control and melioidosis in patients treated at Hospital Teluk Intan in 2024. Notably, 42 cases of melioidosis were reported in Perak during the year. METHODOLOGY A retrospective audit was conducted on all confirmed melioidosis cases from January to December 2024. Data was collected from medical records and laboratory databases. Key variables include patient demographics, HbA1c levels, site of infection, length of hospital stay, ICU admission, and mortality. Patients were stratified based on HbA1c levels to assess glycemic control. RESULT In 2024, a total of 16 melioidosis cases were reported at Hospital Teluk Intan. The majority of patients were male (13), with 3 female patients. The mean age was 55 years. Of the cases, 12 patients were Malay, 1 was Indian, and 3 were foreign nationals. The mortality rate was 37.5% (6 patients), while 10 patients survived, aligning with reported mortality rates of 10–40% for melioidosis. Among survivors, the average hospital length of stay was approximately 20 days. Of the 6 mortality cases, only 1 patient received ICU care due to limited bed availability. Type 2 diabetes mellitus (T2DM) was present in 13 out of 16 cases, with a mean HbA1c of 12.2%. Notably, 3 patients were newly diagnosed with diabetes during admission. Melioidosis was diagnosed through blood cultures in 13 cases, while 3 cases were confirmed via tissue or swab cultures. Only 6 patients reported working in soil-related occupations, while the rest were pensioners or unemployed. Beyond T2DM, 2 patients had chronic kidney disease (CKD), and 1 patient had an underlying gastrointestinal malignancy. CONCLUSION This audit provides valuable insights into the burden of melioidosis in diabetic patients and the impact of glycemic control on disease severity. The findings may inform future clinical practices, emphasizing the importance of optimizing diabetes management to reduce melioidosis-related morbidity and mortality.